Novel potential diagnostic test for Mycobacterium tuberculosis complex using combined immunomagnetic separation (IMS) and PCR-CTPP - S. Intorasoot (2018)
© 2016 The Society for Applied Microbiology Aims: To exploit immunomagnetic separation combined with PCR with confronting two-pair primers (IMS-PCR-CTPP) as a rapid method for detection of Mycobacterium tuberculosis complex (MTC) and identification of Mycobacterium bovis from sputum specimens. Methods and Results: Monoclonal antibody (mAb) against the mycobacterial antigen, 85B (Ag85B), was coupled with magnetic particles for specific immunomagnetic separation (IMS) of Mycobacterium spp. Immunofluorescence assay indicated the capability of mAb to bind to Ag85B in both the recombinant and the native form. The IMS combined with PCR-CTPP targeting the mycobacterial lep B gene was further implemented using 133 sputum samples with acid-fast bacilli grading from negative to 3+. The results showed the sensitivity and specificity of IMS-PCR-CTPP vs gold standard culture method were 89·9 and 88·6% respectively. Conclusions: The IMS-PCR-CTPP method shortens the time for tuberculosis (TB) diagnosis from months to a day. This method is also suitable for investigation of MTC and epidemiological study of Myco. bovis in sputum specimens. Significance and Impact of the Study: This study is the first report emphasizing the combination of IMS and PCR-CTPP for the detection of MTC and simultaneous identification of Myco. bovis from sputum. It could be used for TB diagnosis in resource-limited countries with high TB burden.